Juridical Analysis of the Renewal of the Principle of Legality in Law Number 1 of 2023 - Indah Carmelia; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
This study aims to analyze the level of legal understanding of law enforcement officers regarding the renewal of the principle of legality in Law Number 1 of 2023 and its influence on the perception of legal certainty. The research problem lies in the unequal understanding of officers regarding the change in the concept of the principle of legality from a formal approach to a material approach. The study used a quantitative method with a descriptive analytical design. Data were collected through a Likert-scale questionnaire distributed to 120 respondents consisting of judges, prosecutors, and police investigators using a purposive sampling technique. Data analysis was conducted using descriptive statistics, ANOVA tests, and simple regression with the help of SPSS software. The results showed that the level of legal understanding of law enforcement officers was in the fairly good category with an average score of 3.68. There were significant differences between professions, with judges having the highest level of understanding and investigators having the lowest. The regression results show that legal understanding had a positive and significant effect on the perception of legal certainty. This study provides a scientific contribution by presenting empirical evidence regarding the role of legal understanding in the implementation of the new principle of legality and strengthening the development of empirical-based criminal law studies in legal studies in Indonesia.   Keywords : Principle of Legality, Legal Understanding, Legal Certainty, New Criminal Code, Law Enforcement.